The Economic Value of Carbon Sequestration through Tree Planting in Laos - Vongsikeo, Vongdalone; Breffle, William S.; Apriesnig, Jenny L.; Barkdoll, Brian D. (Asian Development Policy Review, 2020)
Because tree plantations in Laos show that, despite high profitability, tree farmers and private companies face many challenges, including low timber quality, low timber prices, and slow plantation expansion, the aim of this study is to evaluate the social costs and benefits from private tree plantations by considering both market and non-market values, specifically for carbon sequestration. A policy decision tool - specifically cost-benefit analysis – was employed. Existing data from Laos and other locations were used to investigate the economic and social aspects of government policy implications for forest plantation for eucalyptus and teak. A dual-discounting approach was applied to discount future net benefits of market and non-market components to arrive at a present value. We found the monetary benefit of carbon sequestration of teak and eucalyptus tree plantations to be 472.8 million (2020 dollars) over 30 years. It is concluded that the government should intervene by improving systems and regulations that can increase the private rate of return and eventually incentivize the private sector to plant more trees.